MALAYSIA : A PICTORIAL HISTORY 1400-2004 - Moore, Wendy Khadijah (Kuala Lumpur : Archipelago Press, 2004)
Over 1,200 rarely seen, beautiful and fascinating images vividly bring Malaysia's history to life-including maps, prints and engravings before the age of photography; rare hand-coloured glass slides; early photographs of picturesque views and evocative portraits captured in the 1860s by early professional studios; official photographs of royal festivities; amateur attempts to record people, places and wildlife; the shots of press photographs chronicling everyday life as well as major events such as World War II, the Emergency and Independence; and the late 20th century photographers who have documented the country's journey from a largely agrarian community to an industrialized nation. The two-year search for the vivid and unusual resulted in a number of unexpected discoveries whichare reproduced alongside classic images without which no visual history of Malaysia would be complete. Each picture conveys a strong sense of place, and together they tell the story of Malaysia's progress through it's development from that of an ancient trading kingdom to that of a modern independent nation.
Includes index and bibliographical references.
PSZ_JB PSZ_KL PRZS PAGOH
Keywords: Malaysia -- History